Non-Physical Work Environment, Career Development, and Work Motivation on Employee Performance - Deasy Ariati; Nurdjanah Hamid; Andi Kusumawati (Ilomata International Journal of Management, 2023)
Employee performance (EP) is one of the supporting factors in improving the quality of tertiary institutions to support improving services to the academic community. The phenomena in this study are employee dissatisfaction triggered by inadequate non-physical work environment policies, unclear opportunities for career development, and low levels of work motivation which affect performance effectiveness. To what extend are non-physical work environment (NP), career development, and WM on EPer interrelated? A few researchers have explored such relation, especially in the scope of higher education, however, it is inadequate. This study uses different types of data, qualitative and quantitative, whereas the sample and the population comprised civil servants of echelon III and IV at Hasanuddin University with a total of 120 respondents. As for the data analyses method, a multiple linear regression is implemented. The findings showed that NP variables, career development, and WM have a significant effect on EPer. These indicate that career development has a dominant effect on EPer. The results of the study contribute to the development of theory and practice in the areas of work psychology and human resources management.